2015
DOI: 10.1002/esp.3830
|View full text |Cite
|
Sign up to set email alerts
|

Carbon pools in stream‐riparian corridors: legacy of disturbance along mountain streams of south‐eastern Wyoming

Abstract: Streams and their accompanying riparian environments are intrinsic components of terrestrial carbon cycling. However, they have been understudied in terms of the magnitude of their storage components and the role of disturbance in determining carbon storage capacity. This study presents partial carbon budgets for stream-riparian corridors along six study reaches in mountain headwater streams of southeast Wyoming to evaluate the impact of tie-driving, a historic disturbance legacy, on contemporary carbon storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
0
10
0
1
Order By: Relevance
“…Published research has largely focused on temperate regions (Table ; Fig. ), including several studies that examined streams impacted by disturbance (Giese et al ., , Giese et al, ; Fierke and Kauffman, ; Ruffing et al ., in press). Highest values were observed for mesic, old growth, conifer‐dominated riparian forests in the southern Rocky Mountains (Fig.…”
Section: A Review Of Oc Stocks In Riparian Ecosystemsmentioning
confidence: 98%
See 1 more Smart Citation
“…Published research has largely focused on temperate regions (Table ; Fig. ), including several studies that examined streams impacted by disturbance (Giese et al ., , Giese et al, ; Fierke and Kauffman, ; Ruffing et al ., in press). Highest values were observed for mesic, old growth, conifer‐dominated riparian forests in the southern Rocky Mountains (Fig.…”
Section: A Review Of Oc Stocks In Riparian Ecosystemsmentioning
confidence: 98%
“…). At disturbed temperate sites, alteration or removal of riparian vegetation resulted in notably lower OC pools (Giese et al ., , Giese et al ., ; Fierke and Kauffman, ; Ruffing et al ., in press). Mature temperate hardwood forests include a wide diversity of tree and understory species, yet total OC storage in riparian biomass consistently ranges from ~100 to 300 Mg C ha −1 (Table ).…”
Section: A Review Of Oc Stocks In Riparian Ecosystemsmentioning
confidence: 99%
“…Moreover, it is also driven by the temperature [38]. Previous studies have described understory biomass crop as a whole pool [36,39,40], and only a few of them accounted for proportion of functional groups of plant species, e.g., [37,39,41].…”
Section: Introductionmentioning
confidence: 99%
“…Our literature review in Web of Science (string "((((("biomass" AND (((understor* OR "herb layer")) OR "herbaceous")) AND ((dynami* OR season*) OR "time seri*"))) AND ((riparian OR riverine) OR floodplain)))" searched 23 May 2018) revealed 111 studies. Some studies revealed interesting information about herbaceous plant decomposition [46] or biomass of non-forest vegetation [47,48] or forest vegetation [40,49]. However, only two studies focused on the seasonal dynamics of herbaceous biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al () differentiate between the export of fossil and modern POC in the Yellow River, China, and demonstrate how water regulation by dams and sediment storage in reservoirs affect the flux of POC. Examining historical rather than more recent land use, Ruffing et al () investigate the impacts of historical timber harvest and log floating on contemporary carbon storage in mountain streams in Wyoming, USA. They examine the partitioning of carbon among different reservoirs in the river corridor and find that most carbon is stored in live and standing dead trees.…”
mentioning
confidence: 99%